2016
DOI: 10.1007/s40843-016-5047-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-derived nanostructured porous carbons for lithium-sulfur batteries

Abstract: Biomass has been utilized as an energy source for thousands of years typically in the form of wood and charcoal. Technological advances create new methodologies to extract energy and chemicals from biomass. The biomass-derived nanostructured porous carbons (BDNPCs) are the most promising sulfur hosts and interlayers in rechargeable lithium-sulfur (Li-S) batteries. In this article, a comprehensive review is provided in the synthesis of nanostructured porous carbon materials for high-performance rechargeable Li-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 117 publications
0
71
0
Order By: Relevance
“…Integrated micro/nano, hollow, or yolk shell carbon structures have been designed for the enhancement of the conductivity and entrapment of polysulfides . The commonly used strategic approach is to encapsulate sulfur in conductive, high surface area porous carbon framework (e.g., hierarchical porous carbon, graphene/graphene oxides, 1D carbon nanostructures), polymers derived conductive carbon, and noncarbon porous materials (e.g., metal‐organic framework and mesoporous silica (SBA‐15)) to improve the output of the sulfur cathodes. Despite their great potential in enhancing the performance, the existed carbon/sulfur composites have nonpolar nature and poor affinity toward Li 2 S x ( x = 4–8) both of which inevitably cause the decay of rate capability and even the specific capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Integrated micro/nano, hollow, or yolk shell carbon structures have been designed for the enhancement of the conductivity and entrapment of polysulfides . The commonly used strategic approach is to encapsulate sulfur in conductive, high surface area porous carbon framework (e.g., hierarchical porous carbon, graphene/graphene oxides, 1D carbon nanostructures), polymers derived conductive carbon, and noncarbon porous materials (e.g., metal‐organic framework and mesoporous silica (SBA‐15)) to improve the output of the sulfur cathodes. Despite their great potential in enhancing the performance, the existed carbon/sulfur composites have nonpolar nature and poor affinity toward Li 2 S x ( x = 4–8) both of which inevitably cause the decay of rate capability and even the specific capacity .…”
Section: Introductionmentioning
confidence: 99%
“…3). There have been several reviews that expand on these topics and can be found in the references [106][107][108][109][110][111][112][113][114][115][116][117][118] (Fig. 5).…”
Section: Fundamental Studies and Materials Selectionmentioning
confidence: 99%
“…Thus, it is significant to seek green, efficient, low-cost preparation method and renewable raw materials for carbon materials. As carbon-rich precursors, biomass has been considered as a promising candidate in preparation of functional carbon materials because they are bountiful, renewable, non-toxic and low cost [20]. Importantly, the nature usually gives biomass a variety of microstructures, which could be used as precursors for preparing carbon materials with specific structures.…”
Section: Introductionmentioning
confidence: 99%